Perkembangan International Standard of Organization - Suardi Suardi; Fakhruddin Azmi; Nurika Khalila Daulay (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Standards are one of the most important management tools that have emerged and need to be thoroughly studied and understood by scientists, business actors, planners and engineers when designing, selecting, testing or certifying products. Standardization is not a static activity, throughout the world standardization is experiencing developments, both regarding the scope, formulation procedures and their application. All types of standards developed, issued and implemented by national, regional, international organizations or associations, are useful for building a consensus-based culture that is universal and aim to be used by people to communicate with each other, increase and improve mutual understanding between peoples, improve quality live or facilitate trade. Standards are technical specifications or something that is standardized including procedures and methods that are prepared based on the consensus of all parties concerned with due observance of the requirements for safety, security, health, the environment, developments in science and technology, as well as experiences, current and future developments will come to reap the greatest benefits. Standardization is the process of formulating, establishing, implementing and revising standards, which are carried out in an orderly manner through cooperation with all interested parties. The International Standards Organization is a worldwide federation of national standards bodies. ISO is a non-governmental organization composed of standards bodies from more than 167 countries, with one standards body representing each member country.